New-Generation Heterocyclic Bis-Pentamethinium Salts as Potential Cytostatic Drugs with Dual IL-6R and Mitochondria-Targeting Activity - Veronika Talianová; Zdeněk Kejík; Robert Kaplánek; Kateřina Veselá; Nikita Abramenko; Lukáš Lacina; Karolína Strnadová; Barbora Dvořánková; Pavel Martásek; Michal Masařík; Magdalena Houdová Megová; Petr Bušek; et al. (MDPI AG, 2022)
IL-6 signaling is involved in the pathogenesis of a number of serious diseases, including chronic inflammation and cancer. Targeting of IL-6 receptor (IL-6R) by small molecules is therefore an intensively studied strategy in cancer treatment. We describe the design, synthesis, and characteristics of two new bis-pentamethinium salts 5 and 6 (meta and para) bearing indole moieties. Molecular docking studies showed that both compounds have the potential to bind IL-6R (free energy of binding −9.5 and −8.1 kcal/mol). The interaction with IL-6R was confirmed using microscale thermophoresis analyses, which revealed that both compounds had strong affinity for the IL-6R (experimentally determined dissociation constants 26.5 ± 2.5 nM and 304 ± 27.6 nM, respectively). In addition, both compounds were cytotoxic for a broad spectrum of cancer cell lines in micromolar concentrations, most likely due to their accumulation in mitochondria and inhibition of mitochondrial respiration. In summary, the structure motif of bis-pentamethinium salts represents a promising starting point for the design of novel multitargeting compounds with the potential to inhibit IL-6 signaling and simultaneously target mitochondrial metabolism in cancer cells.